The effects of dexamethasone on Tibia development of local chick-Embryo. I: computer-assisted morphometric study - Ali, Wathiq Q.S.; Selman, Mohammad Oda; Al-Hasson, Indaf J.; Al-Ani, Imad Matloub Dally; Al-Salihi, Anam R. (College of Medicine, Al-Nahrain University, 2017)
Dexamethasone is a glucocorticoid as a member of the steroidal anti-inflammatory and immunosuppressant. It has well documented effects on skeletal structures osseous and cartilaginous, commonly used to treat or control diseases. Objective To evaluate by histomorphometric study the effects of dexamethasone on the embryogenesis of long bones in chick embryos. Methods Forty-eight fertile chick eggs of Gallus gallus domesticus, were used. The eggs were divided into 2 groups; control and treated groups of 24 eggs each, these groups were subdivided into 4 subgroups (n=6 eggs). On day 10 of incubation, the control group was injected with 25 μl of distilled water while the treated group was injected with 25 μl of distilled water contained 8 μg dexamethasone. In the next days (11, 12, 13, and 14 of incubation), 12 chick embryos were sacrificed in each day. A computer-assisted morphometric/ image analysis (Motic Image Plus version 2.0ML), was used to measure length, area, perimeter of tibiae, and the area and perimeter of the perichondral osseous collar of cross section in mid-diaphyseal zone of these bones. Results These bones of chick embryos treated with dexamethasone, suffered shortening and retardation in length, weight, area and perimeter throughout the period of this study, decline area and perimeter to the perichondral osseous collar in the mid-diaphyseal zone. Conclusion Dexamethasone given at day 10 of incubation caused tibial bones growth retardation at development stages 11, 12, 13, and 14-days; this was observed in the measured parameters: bone length, area, perimeter and weight.